2022
DOI: 10.1126/sciadv.abm3291
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered grafts exploit axon-facilitated axon regeneration and pathway protection to enable recovery after 5-cm nerve defects in pigs

Abstract: Functional restoration following major peripheral nerve injury (PNI) is challenging, given slow axon growth rates and eventual regenerative pathway degradation in the absence of axons. We are developing tissue-engineered nerve grafts (TENGs) to simultaneously “bridge” missing nerve segments and “babysit” regenerative capacity by providing living axons to guide host axons and maintain the distal pathway. TENGs were biofabricated using porcine neurons and “stretch-grown” axon tracts. TENG neurons survived and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Our large-scale multi-omics analyses (Arcuri et al, 2020;Arcuri et al, 2021;Chauhan et al, 2020;Trzeciecka, Carmy, et al, 2019) combined with computer language processing and machine-learning (Khosla et al, 2021;Myer et al, 2020) has helped identify convergent pathways for axon regeneration and the critical lipids and metabolites in them. The critical knowledge gap is how the first steps of recognition of a target neuron occur by the growing axon and what are the steps in the sequence that results in growth cone collapse leading to formation of an actual functional synapse formation (Skaper et al, 2001;Spencer et al, 1998). Although a number of molecules have been identified that can promote long distance axon regeneration for the visual system but most such molecules are not suitable for delivery.…”
Section: The Current Treatment Modalities and Real Gap Towards Interv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our large-scale multi-omics analyses (Arcuri et al, 2020;Arcuri et al, 2021;Chauhan et al, 2020;Trzeciecka, Carmy, et al, 2019) combined with computer language processing and machine-learning (Khosla et al, 2021;Myer et al, 2020) has helped identify convergent pathways for axon regeneration and the critical lipids and metabolites in them. The critical knowledge gap is how the first steps of recognition of a target neuron occur by the growing axon and what are the steps in the sequence that results in growth cone collapse leading to formation of an actual functional synapse formation (Skaper et al, 2001;Spencer et al, 1998). Although a number of molecules have been identified that can promote long distance axon regeneration for the visual system but most such molecules are not suitable for delivery.…”
Section: The Current Treatment Modalities and Real Gap Towards Interv...mentioning
confidence: 99%
“…Whether the human RGC axons grow together within a “tunnel” and topographically project to the correct brain targets remains unknown. Pigs have been used to test axon regeneration for peripheral nerves (Jones & Redpath, 1998; Smith et al, 2022), there had been consideration of adult monkeys to test axon regeneration (Mertsch et al, 2018), cats, rats and monkeys have been shown to express GAP43 in motor neurons consistent with axon regeneration (Linda et al, 1992). Dog models have been proven to be very helpful to develop therapies for inherited retinal diseases, particularly for Leber's congenital amaurosis (Petersen‐Jones & Komaromy, 2015).…”
Section: Need For Large Animal Validation Studiesmentioning
confidence: 99%
“…Neurites – in particular axons – have been shown to dynamically respond to externally applied forces. For example, growth cone mediated towing, as described above to generate long-distance axons, has been mimicked by applying external towing forces ( Bray, 1984 ; Katiyar et al, 2020 , 2021 ; Smith et al, 2022 ). In one example, “cell puller” machines were shown to extend neurites to a length of up to 960 μm, pulling from the growth cone ( Bray, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic axons (i.e., lacking growth cones) also exhibited growth in response to externally applied mechanical tension. This post-synaptic “stretch-growth” of integrated axons was achieved by motion of a towing membrane to move one population of neurons while another population remained stationary, and demonstrated a remarkable 5–10 cm of axonal elongation at the rate of 8 mm/day ( Smith et al, 2001 , 2022 ; Pfister et al, 2004 ; Katiyar et al, 2019 ). This mechanism of post-synaptic axonal elongation mimics the “second-phase” of axonal growth during development, occurring, for instance, through embryo expansion and ensuing through adolescence due to torso growth and limb lengthening ( Smith et al, 2001 ; Pfister et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…19 Further advancements include incorporating living axon tracts embedded in 3D extracellular matrices, rolled into hollow tubes to serve as nerve conduits. 20…”
Section: Introductionmentioning
confidence: 99%